Aid and the Supply Side: Public Investment, Export Performance and Dutch Disease in Low Income Countries. - Adam, C; Bevan, D (Department of Economics (University of Oxford), 2004)
Contemporary policy debates on the macroeconomics of aid often concentrate on short run Dutch disease effects, ignoring the possible supply side impact of aid financed public expenditure. We present a simple model of aid and public expenditure in which public infrastructure generates an inter-temporal productivity spillover which may exhibit a sector-specific bias. The model also provides for a learning-by-doing externality, through which total factor productivity in the tradable sector is an increasing function of past export volumes. We then use an extended version of this model, calibrated to contemporary conditions in Uganda, to simulate the effect of a step increase in net aid flows. Our simulations show that beyond the short-run, where conventional demand-side Dutch disease effects are present, the relationship between enhanced aid flows, real exchange rates, output growth and welfare is less straightforward than simple models of aid suggest. We show that public infrastructure investment which generates a productivity bias in favour of non-tradable production delivers the largest aggregate return to aid, but it does so at the cost of a deterioration in the income distribution. Income gains accrue predominantly to urban skilled and unskilled households, leaving the rural poor relatively worse off. Under plausible parameterizations of the model the rural poor may also be worse off in absolute terms.